Estrogen Attenuates Chronic Stress-Induced Cardiomyopathy by Adaptively Regulating Macrophage Polarizations via β2-Adrenergic Receptor Modulation - Hou, Hongjian; Adzika, Gabriel Komla; Wu, Qi; Ma, Tongtong; Ma, Yanhong; Geng, Juan; Shi, Mingjin; Fu, Lu; Rizvi, Ruqayya; Gong, Zheng; Sun, Hong (Frontiers in Cell and Developmental Biology, 2021)
Clinical demographics have demonstrated that postmenopausal women are predisposed to chronic stress-induced cardiomyopathy (CSC) and have been associated with the decrease of estrogen. Meanwhile, recent studies have implicated unsolved myocardial proinflammatory responses, which are characterized by enormous CD86+ macrophage infiltrations as an underlying disease mechanism expediting the pathological remodeling of the heart during chronic stress. However, we had previously demonstrated that estrogen confers cardioprotection via the modulation of cardiomyocytes β2-adrenoceptors (β2AR) - Gs/Gi pathways during stress to lessen the incidence of stress-induced cardiovascular diseases in premenopausal women. Intriguingly, macrophages express β2AR profoundly as well; as such, we sought to elucidate the possibilities of estrogen modulating β2AR-Gs/Gi pathway to confer cardioprotection during stress via immunomodulation. To do this, ovariectomy (OVX) and sham operations (Sham) were performed on female Sprague-Dawley (SD) rats. Two weeks after OVX, the rats were injected with 40 μg/kg/day of estradiol (E2). Next, on day 36 after OVX, chronic stress was induced by a daily subcutaneous injection of 5 mg/kg/day of isoproterenol (ISO). E2’s effect on relevant clinical cardiac function indexes (LVSP, LVEDP, +dp/dt and -dp/dt), myocardial architecture (cardiomyocyte diameter and fibrosis), β2AR alterations, and macrophage (CD86+ and CD206+) infiltrations were assessed. In vitro, peritoneal macrophages (PMΦ) were isolated from wild-type and β2AR-knockout female mice. The PMΦ were treated with ISO, E2, and β2AR blocker ICI 118, 551 for 24h, and flow cytometric evaluations were done to assess their phenotypic expression. E2 deficiency permitted the induction of CSC, which was characterized by cardiac dysfunctions, maladaptive myocardial hypertrophy, unresolved proinflammatory responses, and fibrosis. Nonetheless, E2 presence/supplementation during stress averted all the aforementioned adverse effects of chronic stress while preventing excessive depletion of β2AR. Also, we demonstrated that E2 facilitates timely resolution of myocardial proinflammation to permit reparative functions by enhancing the polarization of CD86+ to CD206+ macrophages. However, this adaptive immunomodulation is hampered when β2AR is inhibited. Taken together, the outcomes of this study show that E2 confers cardioprotection to prevent CSC via adaptive immunomodulation of macrophage phenotypes, and β2AR-mediated signaling is crucial for the polarizations of CD86+ to CD206+ macrophages.